Characterization of in vivo biotransformations for trastuzumab emtansine by high-resolution accurate-mass mass spectrometry. Issue 7 (3rd October 2018) - He, Jintang; Yu, Shang-Fan; Yee, Sharon; Kaur, Surinder; Xu, Keyang
ABSTRACT: Trastuzumab emtansine (T-DM1) is an antibody-drug conjugate (ADC) designed for the treatment of HER2-positive cancers. T-DM1 is composed of the humanized monoclonal antibody trastuzumab connected to a maytansine derivative cytotoxic drug, via a nonreducible thioether linker at random lysine residues, and therefore has a very complex molecular structure. It was anticipated that T-DM1 undergoes biotransformations in circulation. However, there was limited knowledge on these structural changes due to bioanalytical challenges. Here, we have investigated the in vivo biotransformations of T-DM1 using a high-resolution accurate-mass (HR/AM) mass spectrometry approach. Three types of biotransformations were characterized for T-DM1 in circulation in tumor-bearing mice, including cysteine or glutathione adduct formation via maleimide exchange, loss of maytansinol via ester hydrolysis, as well as addition of H2 O via linker-drug hydrolysis. These results provide new insights into in vivo catabolism of T-DM1.